Connecting Africa Using the TV White Spaces: From Research to Real World Deployments - Roberts, Sid; Garnett, Paul; Chandra, Ranveer (IEEE LANMAN, 2015)
More than 4 billion people are not connected to the Internet. This is either because there is no infrastructure or because Internet access is not affordable. This digital divide is extreme in Africa. At Microsoft, we have been investigating various technologies to bridge this divide. In this paper we describe our research around the TV White Spaces, and how we have leveraged it, and worked with our partners to connect communities in Kenya, Tanzania, Ghana, Botswana, Namibia and South Africa.